2013
DOI: 10.3389/fnins.2013.00171
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and ghrelin receptor modulation of psychostimulant action

Abstract: Ghrelin (GHR) is an orexigenic gut peptide that modulates multiple homeostatic functions including gastric emptying, anxiety, stress, memory, feeding, and reinforcement. GHR is known to bind and activate growth-hormone secretagogue receptors (termed GHR-Rs). Of interest to our laboratory has been the assessment of the impact of GHR modulation of the locomotor activation and reward/reinforcement properties of psychostimulants such as cocaine and nicotine. Systemic GHR infusions augment cocaine stimulated locomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 163 publications
(313 reference statements)
1
17
0
1
Order By: Relevance
“…; Jerlhag & Engel ; Wellman et al . ; Wellman, Clifford & Rodriguez ), which further supports our hypothesis that ghrelin signaling system regulates reward in general.…”
Section: Discussionsupporting
confidence: 85%
“…; Jerlhag & Engel ; Wellman et al . ; Wellman, Clifford & Rodriguez ), which further supports our hypothesis that ghrelin signaling system regulates reward in general.…”
Section: Discussionsupporting
confidence: 85%
“…These observations point out a role for the ghrelin signaling on HFD sensitization. Interestingly, GHSR-deficient mice also exhibit diminished behavioral activation and reinforcement responses to cocaine and nicotine (Abizaid et al, 2011;Jerlhag and Engel, 2011), and it has been proposed that ghrelin signaling could induce a form of central sensitization in which animals are more reactive to rewarding stimuli (Wellman et al, 2013). Indeed, it has been shown that GHSR-deficient mice display a reduced anticipatory locomotor response to scheduled meals (Blum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Select references are shown but are not meant to be comprehensive. 1–4 Gillard et al, 1993; Hsieh et al, 2006; Hsieh et al, 2005; Kuo et al, 2012; 5–9 Cleary and Docherty, 2003; Harris and Baldessarini, 1973; Heikkila et al, 1975; Holmes and Rutledge, 1976; Kalix, 1983; 10,11 Cleary and Docherty, 2003; Kalix, 1983; 12–14 Estabrooke et al, 2001; Fadel and Deutch, 2002; McPherson et al, 2007; 15,16 Suchankova et al, 2013; Wellman et al, 2013; 17 Murray et al, 2008; 18,19 Jaworska et al, 1994; Kuo et al, 2012; 20,21 Rogge et al, 2008; Vicentic and Jones, 2007; 22 Hao et al, 2004; 23 Mahmood and Lindequist, 2008; 24 Al-Dubai et al, 2006; 25,26 Manberg et al, 1979; Volkoff, 2013; 27 Smith et al, 2008; 28 Morley and Flood, 1987; 29 Morawska et al, 1998; 30 Egecioglu et al, 2013; 31 Tatsuoka et al, 1987; 32–35 Bendotti et al, 1982; Heal et al, 1998; Rech et al, 1984; Sanghvi et al, 1975; 36,37 Kalix, 1984, 1986; 38 Silverstone et al, 1992; 39 Bray, 1993 …”
Section: Figurementioning
confidence: 99%